Education Using Habituation Theory With 6 Step Handwashing Jingle on the Implementation of Handwashing With Soap - Nabilla Pooja Wijonarko; Tavip Dwi Wahyuni; Sugianto Hadi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Most health problems that occur in school-aged children are personal hygiene. Bad habits regarding hand washing will cause the development of disease in children because the germs on the hands have not completely died. So that the material is easy to understand, absorb, accept and implement to form healthy habits, appropriate methods and media are needed for health education as an effort to prevent disease transmission due to poor personal hygiene. Objective: The aim of this research is to determine the effect of education using habituation theory with the 6 step hand washing jingle on the implementation of hand washing with soap. Method: The research design was a pre-experiment with a one group pre-test and post-test design method with a research population of 3 and 4 grade students of 44 people. The sampling technique uses the Slovin formula with a precision of 5% and uses the Probability Sampling formula, namely Stratified Random Sampling with a sample of 40 people. The instrument is an observation checklist sheet and a Likert scale habits questionnaire. Result: It was found that the skills of 15% of students were in the quite skilled category, 55% of students were in the skilled category and 30% of students were in the highly skilled category. Meanwhile, 67.5% of students have positive habits and 32.5% of students have negative habits. The results of data analysis using the Wilcoxon Signed Ranks Test showed that the p-value = 0.000 so p < ? (? = 0.05) wich means education using habituation theory with the 6 steps of hand washing jingle on the implementation of hand washing with soap in children at SDN 2 Bendorejo, Trenggalek Regency is very effective. Conclusion: To obtain good washing hands with soap skills and habits in students, a consistent health promotion program is needed